ECONOMIC AND SOCIAL COMPARISON OF THE ROMANIAN MIDDLE SIZED TOWNS BY HERE AND BEYOND OF THE CARPATHIANS - Kelemen, Réka; Urbánné Malomsoki, Mónika; Lőrinc, Balázs (Studia Mundi – Economica, 2022)
The study focuses on a comprehensive economic and social analysis of small medium-sized towns in Romania. Relevant data from the Romanian National Statistical Office were used for the two years of the study, 2015 and 2019. From the system of basic indicators, a complex development indicator was calculated, in which 15 normalized complex indicators were constructed from 24 basic indicators, divided into three groups of analysis: demographic-social pillar; economical pillar; infrastructural pillar. The aim of the research is to map the situation of small and medium-sized cities in the country, to determine the extent of the actual measurable difference between the cities included in the research and to identify the areas of the country that are considered more liveable, more developed or less developed. To summarise the results, only half of Romania’s small towns and cities have shown real progress compared to themselves. The demographic situation is getting worse in the majority of the cities surveyed, while the general trend is improving in terms of economic and infrastructural quality.